ETHICS AND SECURITY IN ARTIFICIAL INTELLIGENCE AND MACHINE LEARNING: CURRENT PERSPECTIVES IN COMPUTING - Loso Judijanto; Alim Hardiansyah; Opan Arifudin (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
The application of artificial intelligence (AI) and machine learning (ML) continues to show significant development and make a huge impact in various fields, from industry to daily life. However, these technological advancements also come with ethical and security challenges that cannot be ignored. This article explores crucial issues related to data privacy, bias in AI systems, and potential security threats that can arise from the use of AI and ML. From an advanced computing perspective, a comprehensive and collaborative approach between developers, users, and regulators is needed to ensure that the benefits of AI and ML can be optimised without compromising ethical and security standards. This research underscores the importance of developing robust security policies and technologies, as well as implementing methods to reduce bias and protect data privacy to support fair, responsible and safe use of AI.